Regional Economic Outlook, October 2016, Sub-Saharan Africa. (Regional Economic Outlook, 2016)
Economic growth in sub-Saharan Africa this year is set to drop to its lowest level in more than 20 years, reflecting the adverse external environment, and a lackluster policy response in many countries. However, the aggregate picture is one of multispeed growth: while most of non-resource-intensive countries-half of the countries in the region-continue to perform well, as they benefit from lower oil prices, an improved business environment, and continued strong infrastructure investment, most commodity exporters are under severe economic strains. This is particularly the case for oil exporters whose near-term prospects have worsened significantly in recent months. Sub-Saharan Africa remains a region of immense economic potential, but policy adjustment in the hardest-hit countries needs to be enacted promptly to allow for a growth rebound.